Connected and satisfied. The relationship between ethnic connectedness, life satisfaction and ethnic school composition among adolescents from nine ethnic groups. (January 2021) - Mastari, Laora; Spruyt, Bram; Keppens, Gil; Van Droogenbroeck, Filip; Emery, Laura; Siongers, Jessy
Highlights: For adolescents with a migration background, ethnic connectedness is positively related to life satisfaction. The relationship between ethnic connectedness and life satisfaction is moderated by the ethnic school composition. Life satisfaction decreases when adolescents with a migration background don't feel ethnically connected and go to ethnic diverse schools. Abstract: For young people with a migration background it has never been easier to create and maintain a bond with their country of origin (further: feelings of ethnic connectedness). Previous research has already revealed the importance of such feelings of ethnic connectedness for (young) people's subjective well-being. In this study we investigate whether the relationship between the presence and the degree of ethnic connectedness and life satisfaction is moderated by the ethnic school composition. We study this relationship by performing multilevel analyses on 2091 adolescents (aged 14–18 years old) from nine different ethnic groups. Our results shed light on the importance of the ethnic composition of the school in two ways. First, the proportion of adolescents from one's own ethnic group at school is related to higher life satisfaction. Second, the relationship between life satisfaction and the presence of ethnic connectedness is moderated by the extent to which schools are ethnically diverse. More specifically, ethnically diverse schools have a positive influence on the life satisfaction of young people who feel connected to their ethnic group, whereas ethnic diversity at school is negatively related to life satisfaction among young people who do not feel connected to their ethnic group. In the conclusion we elaborate on the implications of our findings.